Analisis Status Mutu Air Sungai Petangkep Dengan Pendekatan Indeks Pencemar - Marchal Susanto; Muhammad Ruslan; Danang Biyatmoko; Kissinger Kissinger (Universitas Lambung Mangkurat, 2021)
The Petangkep River with a flow length of ± 2.3 km has been used since the past until now as a source of clean water and the daily needs of residents for bathing, washing, PDAM raw water and for other activities, on the other hand, the Petangkep River has great potential as a recipient of the impact of industrial activities. There are several activities that can cause pollution in the Petangkep River, namely coal mining, oil palm plantations, community plantations and residential areas. Coal mining activities, if the impacts occur cumulatively, the consequences will not only be limited to pollution of the aquatic environment but also social impacts on the people who still use the river. Until now, the status of water quality is not known, therefore it is necessary to conduct an in-depth study related to pollution in the Petangkep River.